2019
DOI: 10.1002/dmrr.3145
|View full text |Cite
|
Sign up to set email alerts
|

The co‐predictive value of a cardiovascular score for CV outcomes in diabetic patients with no atrial fibrillation

Abstract: Background: Risk factors included in the cardiovascular (CHA 2 DS 2 -VASc) score, currently used for atrial fibrillation (AF), may predispose to cardiovascular events whether or not AF is present. The aim was to explore the predictive role of CHA 2 DS 2 -VASc score on cardiovascular outcomes in diabetic patients without AF.Methods: We accessed individual data from 610 diabetic patients without AF at baseline included in the prospective cohort of the Malmö Diet and Cancer study.Main outcome measure was the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…11 Moreover, we recently found that the CHA 2 DS 2 VASc score was an independent predictor of ischaemic stroke, coronary events and overall mortality in diabetes patients without AF. 24…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, we recently found that the CHA 2 DS 2 VASc score was an independent predictor of ischaemic stroke, coronary events and overall mortality in diabetes patients without AF. 24…”
Section: Discussionmentioning
confidence: 99%
“…Strengths are as follows: the robustness of the data obtained from a large, real-life, adult general population, where severely ill individuals were comprised; the long follow-up duration, with large number of person-years; the reliability of prospectively collected data, with limited loss to follow-up; the stability of the health care and reporting system over time, where adverse events during follow-up were carefully counted through medical history and hospitalization records. 31,32 Limitations are the risk of inclusion bias and residual confounding, and the lack of adjustment for all potential confounders. Approximately 70% of all stroke cases were validated by review of hospital records, but no individual event adjudication was performed for MI.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths are: the robustness of the data related to a large, real-life, adult general population, in which severely ill subjects were not excluded; the long follow-up duration, with consequent high number of person-years; the reliability of the prospective data collection protocol, with limited loss to follow-up; and the consistency over time of the health care system for the included endpoints, where cardiovascular events cases were identified and registered according to careful medical history and hospitalization records. 50 Limitations are represented by a possible inclusion bias, the lack of events adjudication, the lack of adjustments for all potential confounders, and the risk of residual confounding. Moreover, in many cases we had no specific information on concomitant conditions or undiagnosed diseases potentially causing variations in platelet count at baseline.…”
Section: Discussionmentioning
confidence: 99%